2019
DOI: 10.1109/tbme.2018.2850911
|View full text |Cite
|
Sign up to set email alerts
|

Tensor-Based Method for Residual Water Suppression in $^1$H Magnetic Resonance Spectroscopic Imaging

Abstract: A tensor method suppresses residual water simultaneously from all the voxels in the MRSI grid and helps in preventing the failure of the water suppression in single voxels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…To remove the large water signal in waterunsuppressed MRSI we investigated the performance of HLSVD 24,25,40 and Löwner BSS 22 and compared these with results of conventional water-signal suppression during acquisition. In the phantom study, we showed that these post-acquisition water removal methods did not interfere with the quantification of the metabolites of interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To remove the large water signal in waterunsuppressed MRSI we investigated the performance of HLSVD 24,25,40 and Löwner BSS 22 and compared these with results of conventional water-signal suppression during acquisition. In the phantom study, we showed that these post-acquisition water removal methods did not interfere with the quantification of the metabolites of interest.…”
Section: Discussionmentioning
confidence: 99%
“…21 For the water-signal removal, we investigated Hankel Lanczos singular value decomposition (HLSVD) 24,25 and Löwner tensor-based blind source separation (BSS). 22 The performance of these algorithms was compared with each other and with that of conventional water suppression in a phantom and volunteers. Finally, we used the extracted water signal, for absolute metabolite quantification from MRSI's of the prostate recorded with and without water-signal suppression to investigate any effect of this suppression and to reconstruct metabolite maps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, thorough studies are needed to explore accurate matching of estimated sources to the activity they symbolize. The assignment of sources can indeed require a priori knowledge of the activities, such as expecting a certain activity to be prominent over the others (De Vos et al, 2007), or defining frequency bands for dividing the signal subspace (Nagaraja et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent growths in the deep learning (DL) algorithms have shown that models based on convolutional neuronal network (CNN) have a variety of applications on MRS [12][13][14][15][16] . Studies have shown that CNN can be used to sort the spectra according to spectral quality 14,17 .…”
Section: Introductionmentioning
confidence: 99%